The midnight cry: a defense of the character and conduct of William Miller and the Millerites, who mistakenly believed that the second comming of Christ would take place in the year 1844 - Nichol, Francis D. (Review & Herald Publ. Assn., 1945)
This work gives a detailed history and defense of the Advent Movement of the 1840's known as Millerism, the movement from which the Seventh-day Adventist denomination sprang. The book is based on original sources, William Miller's coreespondence, contemporaneous books, pamphlets, journals, newspapers. The first half is devoted to the history of the movement, and the second half to an examination of charges made against the Advent believers, such as that they wore ascension robes, that the Millerite preaching filled the asylums, and so forth. - From the Author to the Reader of This Book.From Cradle to Army Camp.From Doubt to Faith.From Farmer to Preacher.Laying the Groundwork of the Movement.Millerism Spreads to the Great Cities.The Movement Takes Definite Shape.The First Millerite Camp Meeting.The Great Tent is Raised.Interest and Opposition Increase.The Year of the End of the World.The First Disappointment.The Millerite Leaders--Courageous Individualists.Other Millerite Spokesman."Behold the Bridegroom Cometh".Hastening on to the Climax.The Great Day of Hope.The Great Disappointment.Confident in Defeat.The Movement Called Millerism Draws to Its Close.The Kind of World in Which Millerism Flourished.Did the Millerites Indulge in Fanatical Practices.Was Fanaticism Rampant in October, 1844?.Did Millerism Cause Insanity, Suicide, and Murder?.Old Asylum Records Offer Further Testimony.Did the Millerites Wear Ascension Robes?.Tracing the Robe Story Through the Years.The Robe Story in Twentieth Century Dress.Did the Millerites Set Forth Strange, New Beliefs?.Did the Advent Faith Miller Kindled, Die with Him?.The Case for the Defense Summed Up.Acknowledgments.Appendices.Bibliography.Index